(3TQM GdCYTGH hGdYbGbjQs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje , hUdi Gddge Ydi SjOfG eMeO hYdi Bdg hSde gPG JaSjQ GdCYTGH hGdYbGbjQ , hebJWakG ef QjMGfI GdLjhH ai GdYbGbjQ hGdYThH s
(3BNQgG (B:s
(3hGdBNQ SaQLd GdgfO hgeG bdjdG GdhLhH HGdeZQH CfgeG ef HfGJ GdgfO hGdUjf , HOdg RfLHjd hgj GdTLQI GdePchQI ai bhdg JYGdi (B" (3RjJhfI dG TQbjI hdG ZQHjI (B" s
(3Vef eLehY s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B129 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs